Isolated primary hydatid disease of thyroid presenting as a solitary nodule: A rare case report (Indian Journal of Case Reports, 2019)
Echinococcosis is a significant health problem in endemic areas with a prevalence rate of 2–6%. Hydatidosis is reported in the liver in 70% of cases and lungs 15%, and rarely <1% are reported in breast, bones, gallbladder, pancreas, thyroid, and ovaries. Primary hydatid cyst of the thyroid is a rare clinical entity. Review of literature reveals <60 cases of isolated hydatid cyst of the thyroid. Here, we present the case of primary hydatid cyst in thyroid presenting as a solitary nodule. Uncommon presentation of thyroid in endemic areas during initial radiological workup should raise suspicion and warrant careful further evaluation. Immunologic tests have low sensitivity and specificity and, hence, have a limited role. Neck ultrasonography demonstrating daughter cysts is characteristic of hydatid cyst. Although enucleation and intracystic injection of albendazole are suggested, excision of cyst avoiding spillage of contents is currently the approved treatment strategy. Surgical excision with perioperative albendazole gives excellent results with low recurrence.